ANALISIS PERAN KEPALA SEKOLAH DALAM PEMBERDAYAAN GURU: SEBUAH UPAYA PENINGKATAN MUTU PENDIDIKAN - Nyoman Wardana (LP3M Universitas PGRI Mahadewa Indonesia, 2019)
The prolonged economic, political and belief crisis that hit the Indonesian nation has had an impact on almost all aspects and order of life. Although it has caused a lot of deterioration to the nation and the people, one of the positive lessons that emerged was the emergence of basic thinking that fosters reform in various aspects of national life and statehood. The main focus of this reform is to create a civil society in the life of government, society and countries that have values ​​of